Association of circulating Progesterone Receptor Membrane Component-1 (PGRMC1) with breast tumor characteristics and comparison with known tumor markers. Issue 2 (February 2020) - Ruan, Xiangyan; Cai, Guiju; Wei, Yun; Gu, Muqing; Zhang, Ying; Zhao, Yue; Mueck, Alfred O.
Abstract: Objectives: Progesterone receptor membrane component-1 (PGRMC1) expressed in breast cancer tissue has been suggested to predict a worse prognosis. The aim of this study was to assess for the first time if blood concentrations of PGRMC1 are also associated with receptor status, tumor diameter, grading, and lymphatic status. The second aim was comparison with known tumor markers. Methods: A total of 372 women, including 278 patients with invasive breast cancer, 65 with benign breast disease, and 29 healthy women (control), were recruited. PGRMC1 blood concentrations were measured by a recently developed enzyme-linked immunosorbant assay, and were correlated to predictive tumor characteristics and compared with serum carcinoembryonic antigen (CEA), CA125, and CA153. Results: PGRMC1 levels in the cancer group were significantly higher than in the control and benign group and increased with higher cancer stages ( P  < 0.05). PGRMC1 concentrations in the estrogen receptor (ER)+/progesterone receptor (PR)+ group were higher than in the ER−/PR− group, related to larger tumor diameter and the presence of lymph node metastasis ( P  < 0.05). Multivariable linear regression analysis was used to control the confounding factors. Tumor diameter, lymphatic metastasis, and ER (but not PR) were positively associated with PGRMC1 ( P  < 0.05). The receiver-operating characteristic curve (ROC) analysis was used to assess area under the curve (AUC). AUC was 87.9% for stages III+IV and 80.8% for stages I+II ( P  < 0.01). ROC did not find significant effects on AUC for CA125, only significant for CEA and CA153 for stages III+IV. Conclusion: As PGRMC1 levels are positively associated with breast tumor characteristics known to predict a worse diagnosis, PGRMC1 may be valuable as a new tumor marker, and superior to CEA, C125, and CA153. Because of the positive association with ER-expression, PGRMC1 may interact with this receptor. Abstract : Supplemental Digital Content is available in the text